Using Google Meet in Group Discussions to Improve Learning Activities And Students' Problem-Solving Ability During the COVID-19 Pandemic - Marsini Marsini; Dwikoranto Dwikoranto (IJORER : International Journal of Recent Educational Research, 2022)
Improvements have been made to online learning during the COVID-19 pandemic through GMeet due to restrictions on crowding and maintaining distance between students, while learning must continue. This study aims to improve student learning activities and problem-solving abilities. Improvement of learning through classroom action research. Data were analyzed descriptively. The instruments are in the form of a Problem Solving Ability Test sheet and an Observation Sheet. The results of improving the use of GMeet learning in group discussions which in its implementation combined with WhatsApp and Google forms can improve student learning activities and problem-solving abilities. The increase in student learning activities in the first cycle, the percentage of student activity was 66% in sufficient criteria to 80% in good criteria in the second cycle. This shows that the percentage of student activity has increased and has reached the predetermined indicators of success. This increase in problem-solving ability can be seen in the average class value and the increase in the percentage of completeness after being given treatment. In the first cycle, the average value is 65 with a percentage of 65%, the and second cycle is an average of 80.25 with a percentage of 80%.